Interaction effects of oxytocin receptor gene polymorphism and depression on hippocampal volume. (30th December 2018) - Na, Kyoung-Sae; Won, Eunsoo; Kang, June; Kim, Aram; Choi, Sunyoung; Kim, Yong-Ku; Lee, Min-Soo; Ham, Byung-Joo
Highlights: There are significant interaction effects between OXTR and MDD for hippocampal volumes. Healthy controls with AA genotype had significantly larger hippocampal volumes than healthy controls with G allele types. The A allele was dominant in both groups. Abstract: Many studies have revealed that the oxytocin receptor gene (OXTR) is associated with emotional salience and depression among females. Hippocampus is closely associated with the pathophysiology of major depressive disorder (MDD). However, little is known of the interaction effects of OXTR and MDD on hippocampal volume. We sought to investigate the interaction effects of OXTR (rs53576) allelic variants and MDD on hippocampal volumes which also including subfield volumes. The OXTR rs53576 genotype groups were categorized as minor G allele carriers and A allele homozygotes. A total of 47 female patients with depression and 30 healthy females were included in this study. There were significant interactions between OXTR allele type and diagnosis of MDD on the 7 hippocampal subfield volumes, such as left presubiculum, left subiculum, left molecular, right cornus ammonis 1, right granule cells in the molecular layer of the dentate gyrus, right molecular layer, and right subiculum. There were no differences in the hippocampal volumes between MDD vs healthy controls or OXTR A vs G alleles. Our results demonstrate the importance of the interactions between OXTR and MDD on hippocampal volume. Future studies with large sample size should expand those interactions in the whole brain volumes.